Dry sliding wear behaviour of Al –5Si-3Cu-0.5Mn alloy and its WC reinforced composites at elevated temperatures. (2021) - Sharath Kumar, P.N.; Sachit, T.S.; Mohan, N.; AkshayPrasad, M.
Abstract: Sliding wear behavior of Al-5Si-3Cu-0.5Mn (LM4) alloy and its composites reinforced with WC particles are investigated at room as well as elevated temperatures. Wear test were performed at fixed sliding distance of 200 rpm, track dia of 40 mm and applied load of 10 N to 40 N with test duration of 10 min. To understand the effect of temperature on wear rate, worn surface morphology was studied using Scanning electron microscopy and EDS (Energy dispersion spectroscopy). At room temperature the increased wear resistance was observed at higher weight percentage of WC particles. At elevated temperature the wear resistance of the composites decreases when temperature increases. The friction coefficient of the composites was studied. The wear analysis of worn surface depicts the possibility of different wear mechanisms like abrasive and delamination type wear mechanisms.